Selection of papers presented at the symposium MPLP-2018 : Broadband mid-IR source based on a MgO : PPLN optical parametric oscillator. (14th February 2019) - Kolker, D B; Sherstov, I V; Kostyukova, N Yu; Boyko, A A; Erushin, E Yu; Nyushkov, B N
Abstract: We have designed and tested a broadband fan-out PPLN-based optical parametric oscillator (OPO) pumped by a Q-switched Nd : YAG laser (1.064 μm) and operating in the spectral range 2.6–4.2 μm. The optical scheme of the OPO utilises a cylindrical pump beam expander for increasing the effective aperture of the PPLN structure and obtaining broadband generation.